2020
DOI: 10.4314/ijbcs.v14i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin contamination of herbal medications on sale in Ebonyi State, Nigeria

Abstract: The practice of herbal medication is as old as the culture of the people and despite the advent of modern medication, many people of south eastern Nigeria, still patronizes herbal medication. Herbal medications are consumed directly and could be contaminated with mycotoxins which are detrimental to human and animal health. This study was therefore, designed to determine the extent of mycotoxin contamination of herbal medications on sale in Ebonyi State, South-Eastern Nigeria. In this regard, a multistage rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…In this study Aspergillus fungi recorded the highest level in fungal isolates, this is attributed to its widespread in the environment by ability to produce huge numbers of asexual reproductive units and its ability to grow in all environments and endure bad conditions (Pitt & Hocking, 1997). The results are consistent with ( Idu et al, 2011;Ikeagwulonu et al, 2020)…”
Section: Fungal Contaminationsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study Aspergillus fungi recorded the highest level in fungal isolates, this is attributed to its widespread in the environment by ability to produce huge numbers of asexual reproductive units and its ability to grow in all environments and endure bad conditions (Pitt & Hocking, 1997). The results are consistent with ( Idu et al, 2011;Ikeagwulonu et al, 2020)…”
Section: Fungal Contaminationsupporting
confidence: 92%
“…There are many herbs that studies have indicated to be effective as a treatment for diabetes, such as Ferula assafoetida, Annona squamosal, Zingiber officinale, Gymnema But it should be noted that many of the herbal mixtures used to treat diseases that are sold in local stores and markets are contaminated with many sources of danger, such as Mycotoxigenic Fungi and Mycotoxins (Abed et al, 2020 ;Ikeagwulonu et al, 2020), As well as bacteria and heavy metals (Zamir et al, 2015;Abualhasan et al, 2019). The aim of the current study is to detect the presence of fungal contamination and mycotoxins in some of selected antidiabetic herbs mixtures are widely spread among Iraqis in Diyala Governorate population.…”
Section: Introductionmentioning
confidence: 99%
“…The OTA concentration from this study was higher than the results of Roy and Kumar [ 56 ] who reported that 44% of 129 herbal samples destined for Ayurvedic medicines were contaminated with OTA (range 0.3–0.00234 µg/kg). Aziz et al, reported higher OTA levels compared to our findings; in their study, 3 out of 17 medicinal plant samples were contaminated by OTA at a mean concentration of (20–80 µg/kg [ 25 ]).…”
Section: Discussioncontrasting
confidence: 53%
“…Furthermore, the control of mycotoxins is inadequately funded, and many African governments do not give priority to mycotoxin control in medicinal plants [ 18 ]. However, the occurrence of mycotoxins has been reported in South Africa [ 16 , 17 ]; Kenya [ 19 , 20 , 21 ]; Nigeria [ 22 , 23 , 24 , 25 ]; and Egypt [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have highlighted the central role of plant multiplication materials (seeds, cuttings, grafts) in the prevalence of plant diseases (Mathur and Kongsdal, 2003;Zida et al, 2008;Bonzi et al, 2012a). In addition to these negative effects on the productivity of the plants, the fungi carried and transmitted by the seeds mostly produce some mycotoxins (Ikeagwulonu et al, 2020) which deteriorate the nutritive quality of foods (De Marinis et al, 2019). In Burkina Faso, vegetable seeds in general, and onion seeds in particular, are mainly imported.…”
Section: Introductionmentioning
confidence: 99%